Transport and logistics potential as a factor of investment attractiveness of the Odesa region: the role of seaports, railway and road corridors, and international transport projects - Iran, K.; Kudelina, S. (Journal of Education, Health and Sport, 2025)
The article explores the role of the transport and logistics potential of the Odesa region as a key factor of its investment attractiveness. Emphasis is placed on Odesa’s strategic geographical location on the Black Sea coast, its integration into international transport corridors, and the functioning of seaports, railway hubs, and highways that ensure the region’s connectivity with global markets. The study analyzes the dynamics of port cargo turnover, identifies problems of infrastructure development, and outlines the significance of international transport projects for attracting investment. Particular attention is given to the challenges of wartime conditions and the prospects for post-war recovery of the logistics sector.